Reprogramming primordial germ cells into pluripotent stem cells. - Gabriela Durcova-Hills (PLoS ONE, 2008)
Background Specification of primordial germ cells (PGCs) results in the conversion of pluripotent epiblast cells into monopotent germ cell lineage. Blimp1/Prmt5 complex plays a critical role in the specification and maintenance of the early germ cell lineage. However, PGCs can be induced to dedifferentiate back to a pluripotent state as embryonic germ (EG) cells when exposed to exogenous signaling molecules, FGF-2, LIF and SCF. Methodology and principal findings Here we show that Trichostatin A (TSA), an inhibitor of histone deacetylases, is a highly potent agent that can replace FGF-2 to induce dedifferentiation of PGCs into EG cells. A key early event during dedifferentiation of PGCs in response to FGF-2 or TSA is the down-regulation of Blimp1, which reverses and apparently relieves the cell fate restriction imposed by it. Notably, the targets of Blimp1, which include c-Myc and Klf-4, which represent two of the key factors known to promote reprogramming of somatic cells to pluripotent state, are up-regulated. We also found early activation of the LIF/Stat-3 signaling pathway with the translocation of Stat-3 into the nucleus. By contrast, while Prmt5 is retained in EG cells, it translocates from the nucleus to the cytoplasm where it probably has an independent role in regulating pluripotency. Conclusions/significance We propose that dedifferentiation of PGCs into EG cells may provide significant mechanistic insights on early events associated with reprogramming of committed cells to a pluripotent state.